2022
DOI: 10.1590/s1980-657420220002422
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary postmenopausal women not undergoing hormone replacement therapy can have their blood pressure lowered by performing resistance training: a systematic review and meta-analysis of randomized controlled trials

Abstract: This systematic review and meta-analysis aimed at examining the literature regarding the effects of resistance training (RT) on blood pressure (BP) in postmenopausal women. Methods: The Pubmed, Scopus, Embase, and BVS databases were accessed by two independent reviewers between July 2020, and June 2021 to search for studies that investigated the effects of RT on BP. The eligibility criteria were determined by the PICOT strategy. P: postmenopausal women, I: RT, in which training variables are presented, C: pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A recent trial supported that combined exercise training among postmenopausal women can lead to great reduction of blood pressure (BP) [25]. Furthermore, a meta-analysis reported that postmenopausal women with resistance training without hormone therapy had lower blood pressure than those in the control group [26]. A randomized, parallel dietary intervention study showed that Low-sodium Dietary Approaches to Stop Hypertension (DASH) diets can lead to reducing BP among postmenopausal women [27].…”
Section: Introductionmentioning
confidence: 99%
“…A recent trial supported that combined exercise training among postmenopausal women can lead to great reduction of blood pressure (BP) [25]. Furthermore, a meta-analysis reported that postmenopausal women with resistance training without hormone therapy had lower blood pressure than those in the control group [26]. A randomized, parallel dietary intervention study showed that Low-sodium Dietary Approaches to Stop Hypertension (DASH) diets can lead to reducing BP among postmenopausal women [27].…”
Section: Introductionmentioning
confidence: 99%